Energy and water balance studies in the boundary layer over Delhi (India) - DAS, Yashvant; PADMANABHAMURTY, Bamapati; MURTY, Aipillay Satya Narayana (Contributions to Geophysics and Geodesy, 2009)
This paper describes the computation of various ﬂuxes of energy and water balance components in the boundary layer over Delhi, for the years 1997–98 and 1998–99. Bulk-aerodynamic method has been used for the computation of sensible heat (H ) and latent heat (LE) ﬂuxes. Soil heat ﬂux (G) has been directly measured using heat ﬂux plate and also estimated using conductivity equation for comparison. Book-keeping procedure of Thornthwaite’s has been used for water balance evaluation. Potential evapotranspiration (PE) is computed using Thornthwaite’s method and compared with Penman’s for the representative station. The results of the computed ﬂuxes of energy and water balance components were compared with UREMBS-94 (Urban Rural Energy and Moisture Balance Studies - ES/63/018/84 – 1994) results for both the winter and summer seasons for urban (dry) and rural (moist) areas. It was found that there persists an energy imbalance in both the seasons for urban/dry as well as rural/moist areas. However, urban areas showed positive (+V e) energy imbalances and act as heat/pollution sources, whereas the rural/moist areas showed negative (−V e) energy imbalances and act as heat/pollution sinks. These results are in good agreement with the UREMBS–94 results. On the other hand, water balance analysis for urban/dry and rural/moist areas showed the same ranges of moisture indices indicating hardly any shift in climate. However, UREMBS–94 results showed climatic shift in the urban regions.